2016
DOI: 10.1111/aor.12725
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Investigation of an Axial Rotary Blood Pump

Abstract: Left ventricular assist devices (LVADs) have become a standard therapy for patients with severe heart failure. As low blood trauma in LVADs is important for a good clinical outcome, the assessment of the fluid loads inside the pump is critical. More specifically, the flow features on the surfaces where the interaction between blood and artificial material happens is of great importance. Therefore, experimental data for the near-wall flows in an axial rotary blood pump were collected and directly compared to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 38 publications
0
21
0
1
Order By: Relevance
“…The specific speed, flow coefficient, and head coefficient are automatically maintained under the applied Euler and Reynolds scaling. A comparison between the pump performance curves of the up-scaled model and the original model has shown similarity based on pump pressure head, rotational speed and volume flow at the investigated state of operation (30). Therefore, it is concluded that both pumps have similar flow and that the slightly larger tip gap in the up-scaled model did not significantly alter the mean flow characteristics of the pump.…”
Section: Methodsmentioning
confidence: 99%
“…The specific speed, flow coefficient, and head coefficient are automatically maintained under the applied Euler and Reynolds scaling. A comparison between the pump performance curves of the up-scaled model and the original model has shown similarity based on pump pressure head, rotational speed and volume flow at the investigated state of operation (30). Therefore, it is concluded that both pumps have similar flow and that the slightly larger tip gap in the up-scaled model did not significantly alter the mean flow characteristics of the pump.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the gap size of the hydrodynamic bearing in the HVAD is generally smaller than 0.05 mm, 16 and the gap size between the blade tips and the housing in the HM II pump is 0.1 mm. 50 Therefore, the inaccuracies in the geometries of the two pumps could potentially cause noticeable changes in the WSS levels in these gaps. The CFD-predicted HI in the areas with small gaps could also be affected.…”
Section: Discussionmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) has been widely used in various engineering fields to solve and analyze problems that involve fluid flows . Empirical hemolysis estimation models, in conjunction with CFD simulations have been used to predict hemolysis during the development phase of VADs . Typical hemolysis models relate hemolysis to shear stresses and exposure time through a power‐law relationship D%=hbHb×100=Cταtβ,…”
Section: Empirical Constants Of Some Power‐law Modelsmentioning
confidence: 99%
“…Computational fluid dynamics (CFD) has been widely used in various engineering fields to solve and analyze problems that involve fluid flows (6,7). Empirical hemolysis estimation models, in conjunction with CFD simulations have been used to predict hemolysis during the development phase of VADs (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Typical hemolysis models relate hemolysis to shear stresses and exposure time through a power-law relationship (18)(19)(20)(21)(22) where D (%) is the hemolysis index, Hb is the total hemoglobin concentration, hb represents the increase in plasma free hemoglobin, C, and are empirical constants determined by regression of the experimental data.…”
mentioning
confidence: 99%